It infrastructure transformation model prioritization and selection at pt telkomsel using analytic hierarchy process (ahp) - Rizki Hanafi, Perdana; P.K. Bintoro, Bambang; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2018)
Abstract - PT Telekomunikasi Selular (Telkomsel) is the largest telecommunication operator in Indonesia and gets ranked 7th in the world in which its customers are 196.3 million and reaches 100% of all regions in Indonesia. In the telecommunication industry, the last few years are difficult times for all telecommunication operators since technology and customer’s behaviour have changed. The business of telecommunication company has shifted away from SMS and voice services to data service. Telkomsel is aware that the transformation from all lines must be performed to follow the change, from traditional telecommunication company to the digital business-oriented company. IT Infrastructure Management division as one of the units in the organization of Telkomsel attempts to articulate the grand design of digital transformation in a plan of IT Infrastructure transformation model to adjust to the need of digital business. This research aims to plan the decision-making model in selecting a proper IT Infrastructure transformation model for IT Infrastructure Management division. This research used the Analytical Hierarchy Process (AHP) method in which a problem is compiled in a systematic hierarchy. Data were taken with qualitative and quantitative methods through interview and questionnaire. As the output from a series of AHP processes conducted in this research, it can be concluded that this AHP method is highly effective to be used for supporting decision-making process in selecting a proper transformation model to answer the readiness of IT Infrastructure Management in supporting the need of business in the digital world.Keywords: multi-criteria decision making, Analytical Hierarchy Process, IT Infrastructure, Telecommunication, Model Transformation